TITIK KRITIS HALAL & NILAI TAMBAH KOPI JAHE TERIPANG HALAL CRITICAL POINT & ADDED VALUE GINGER BEAM COFFEE - Hadistio, Alfin; Siti Irma Rahmawati (Universitas Djuanda, 2020)
The use of sea cucumbers as an additive to coffee can add to the variety of herbal coffee products. In a published study, it was stated that consumers tended to prefer sea cucumber ginger coffee, and an observation was made of the composition of sea cucumber ginger coffee on the parameters of ash content and pH. As well as for other parameters, observations were made of the dissolution rate, infusion rate and water content. By meeting the Indonesian National Standard, coffee has the opportunity to increase profits or added value. This study aims to discuss the critical point of halalness and to get the added value of sea cucumber ginger coffee products. The Hayami method is used to calculate the added value of the product under study. The results show that the profit rate is 43% and the added value of the product is Rp. 625,858 kg. The analysis shows that sea cucumber, ginger and coffee, when combined can provide added value which is very profitable for small industries Keywords:, halal coffee, hayami, sea cucumber